Phosphosulindac (OXT-328) prevents and reverses chemotherapy induced peripheral neuropathy in mice - Basu, Aryah; Yang, Jennifer Y.; Tsirukis, Vasiliki E.; Loiacono, Andrew; Koch, Gina; Khwaja, Ishan A.; Krishnamurthy, Mahila; Fazio, Nicholas; White, Emily; Jha, Aayushi; Shah, Shrila; Takmil, Cameron; et al. (Frontiers in Neuroscience, 2024)
Background Chemotherapy-induced peripheral neuropathy (CIPN), a side effect of chemotherapy, is particularly difficult to treat. We explored whether phosphosulindac (PS), a modified NSAID, could treat CIPN. Methods CIPN was induced in male C57BL/6 J mice by paclitaxel, vincristine or oxaliplatin. Mechanical allodynia was measured with the von Frey test and cold allodynia with the acetone test. To determine the preventive effect of PS, it was administered 2 days before the induction of CIPN. Mouse Lewis lung carcinoma xenografts were used to determine if PS altered the chemotherapeutic efficacy of paclitaxel. Cultured cell lines were used to evaluate the effect of PS on neuroinflammation. Results Treatment with each of the three chemotherapeutic agents used to induce CIPN lowered the mechanical allodynia scores by 56 to 85% depending on the specific agent. PS gel was applied topically 3x/day for 16–22 days to the hind paws of mice with CIPN. This effect was dose-dependent. Unlike vehicle, PS returned mechanical allodynia scores back to pre-CIPN levels. PS had a similar effect on paclitaxel-induced CIPN cold allodynia. Sulindac, a metabolite of PS, had no effect on CIPN. PS significantly prevented CIPN compared to vehicle. Given concomitantly with paclitaxel to mice with lung cancer xenografts, PS relieved CIPN without affecting the anticancer effect of paclitaxel. The enantiomers of PS were equally efficacious against CIPN, suggesting the therapeutic suitability of the racemate PS. There were no apparent side effects of PS. PS suppressed the levels of IL-6, IL-10, CXCL1, and CXCL2 induced by paclitaxel in a neuroblastoma cell line, and macrophage activation to the M1 proinflammatory phenotype. Conclusion Topically applied PS demonstrated broad therapeutic and preventive efficacy against CIPN, preserved the anticancer effect of paclitaxel, and was safe. Its anti-CIPN effect appears to be mediated, in part, by suppression of neuroinflammation. These data support further evaluation of topical PS for the control of CIPN.